Pemanfaatan Canva Sebagai Alat Pengembangan Kreativitas Remaja Dalam Mewujudkan Generasi Muda Yang Kreatif dan Inovatif: Studi Kasus KKN di SMPN 32 Surabaya - Rafi Purwa Syahputra; Salma Nabila; Jannatuzzahra, Khoirunisa; Amalia Anjani Arifiyanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The development of interactive learning media is the key to creating quality students. Canva as design application is an effective tool in creating interactive learning media in schools. KKN activities at SMPN 32 Surabaya aim to develop students' creativity through the Canva application to create a creative and innovative generation and realize responsive learning. The activity was held on Thursday 30 November 2023 involving 30 participants from class 7E of SMPN 32 Surabaya. Activities are carried out using a participatory method with 3 implementation stages, namely program planning, program implementation and program assessment. The results of this activity received a positive response with a satisfaction level reaching 78%. Survey results show that 70% of participants will use Canva as a learning medium and 53% of participants will use Canva as a tool to develop creativity.